Pengaruh Faktor Adaptasi Model UTAUT terhadap Intensi Adopsi Sistem Hijau pada Bank Indonesia - Kaeksi, Racana Ayu; Maghfiroh, Intan Sartika Eris; Akbar, Muhammad Aminul (Jurnal Buana Informatika, 2025)
Bank Indonesia (BI) plays a strategic role in promoting a green financial system, yet faces internal challenges in adopting environmentally sustainable technologies, as reflected in its low “leading by example” score in the Green Central Banking Scorecard. This study applies an adapted UTAUT model, incorporating stakeholder engagement, to examine green Information Systems (IS) adoption at BI. PLS-SEM results show stakeholder engagement significantly influences adoption (β = 0.792, p < 0.001) and performance expectancy positively affects behavioral intention (β = 0.420, p = 0.014). In contrast, facilitating conditions negatively impact adoption (β = –0.374, p = 0.027), indicating limited resource support. Effort expectancy and social influence are not statistically significant. Stakeholder feedback suggests BI remains at the initial stage of green IT maturity (level 1: incipient), highlighting the need for stronger institutional and government support and clearer implementation strategies to advance its green digital transformation.